Supercritical enhanced atomization induced particle entrapment for continuous production of injectable micro and nano-suspensions - Snehashis Nandi; Alain Collas; Lidia Tajber; Luis Padrela (Journal of CO2 Utilization, 2024)
The production of micro- and nanosized dry powder formulations of pharmaceutical drugs by spraying methods with high yields and desired rheological characteristics is typically challenging from laboratory up to commercial scales. In this work, supercritical CO2 was used in a supercritical enhanced atomization (SEA) process as a bottom-up method to create micro- and nanoparticles, with an enhanced control over their physicochemical properties, to produce injectable aqueous suspensions of itraconazole (ITZ). The existing drying chamber design was optimized to significantly improve the SEA process product yield. Additionally, a novel set-up was integrated for the continuous production of ITZ particles directly collected in an aqueous stabilizer media by the supercritical enhanced atomization-induced particle entrapment into suspension (SEA-PES) process. To evaluate the influence of various SEA-PES processing parameters on the particle size, morphology, residual solvent, and particle collection yield of each experimental run utilising the in-house built continuous set-up, a solvent screening study followed by a design of experiments (DoE) was carried out. Based on the given output parameters, tetrahydrofuran (THF) was selected as the optimum solvent for ITZ. The best excipient/s for stabilising ITZ micro- and nanoparticles in suspension, respectively, have previously been discovered to be vitamin E TPGS (0.5% w/w) in combination with PVP K30 (0.5% w/w). Using both the SEA and SEA-PES methods, homogeneous ITZ micro- and nanosuspensions (solid content of 200 mg/g) with D50 0.23 ± 0.06 μm and 3.5 ± 0.2 μm were produced, respectively. These suspensions were stable and resuspendable after 365 days of storage at 25 °C. Finally, utilising a newly developed discriminatory dissolution method, the in vitro release characteristics of ITZ micro- and nanosuspensions were evaluated. There was no significant difference between the SEA and SEA-PES methods to generate the drug micro- and nanosuspensions, according to both solid-state and in vitro release profiles analysis. This work provides proof of concept for establishing a cost-effective experimental platform for the continuous production of injectable micro-and nanosuspensions of ITZ.